(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Thirty species of fusulinids belonging to 14 genera: Pamirina, Boultonia, Quasifusulina, Darvasites, Rugosofusulina, Darvasella, Dutkevitchia, Robustoschwagerina, Zellia, Alpinoschwagerina, Chalaroschwagerina, Pseudofusulina, Chusmella, and Rugosochusenella are described from separate samples of carbonate rocks widely developed in the vicinity of Ankara. Seven species among them are new. Two fusulinid assemblages - Sakmarian and Yahtashian - were revealed and characterized for the first time for Turkey.